Mumps-specific antibody persistence in children aged 3–7 years immunized with two doses of mumps-containing vaccines: A prospective cohort study in Jiangsu Province, China - Jinfang Sun; Mingma Li; Lei Zhang; Xiuying Deng; Ying Hu; Qiang Chen; Zhiguo Wang; Xiang Sun; Yuanbao Liu (Human Vaccines & Immunotherapeutics, 2023)
Mumps reemergence has been reported in developed countries with high levels of two-dose mumps-containing vaccine (MuCV) coverage. The effectiveness of the two-dose MuCV may be compromised by limitations in the persistence of immunity. This prospective cohort study evaluated the persistence of immunity of a two-dose MuCV in children aged 3–7 years from 2015 to 2020. Persistence of antibody to mumps, determined as the geometric mean antibody concentration (GMC), and seropositivity were analyzed for both repeated measurements from three follow-ups and on each cross-section, respectively. A total of 105 eligible subjects were recruited. Their overall seropositivity rate was relatively high and stable (92.4%–84.8%), while the overall GMC decreased from 547.6 U/ml to 333.3 U/ml. Analysis of waning immunity in 91 participants showed a significant and consistent downward trend for GMC, which differed significantly in boys and girls. The overall seropositivity rate decreased slightly from 2015 (95.6%) to 2016 (92.3%) but both were significantly higher than in 2018 (84.6%). The rates in girls remained stable, while those in boys declined to 75% in 2018. The seropositivity rate of the cross-section level decreased from 95.4% to 86.4% in 4 years. Although two-dose MuCV may result in a high level of immunity, antibody concentrations decay over 2 years after the second dose. Children with waning immunity after receiving two doses, especially boys, require further surveillance at 4 years and later to avoid future mumps epidemics. Clinical trial registration: NCT02901990.